Simulasi Kekuatan Mata Pisau Traktor Pemanen Jagung dengan Variasi Sudut Menggunakan Solidwork - Harahap, Doa; Waskito, Waskito; Nurdin, Hendri; Rifelino, Rifelino (Lembaga Yasin AlSys, 2024)
The corn harvesting tractor is one of the innovations in agricultural technology. However, there is a problem where the harvesting blade is broken and wears out quickly. One of the factors causing the problem is the angle of inclination of the blade. The smaller the angle of inclination of the blade, the sharper it is but the risk of being easily broken and worn out. For this reason, it is necessary to test the value of the blade slope which has a good strength value. Before this knife is made directly, it is necessary to design and simulate the strength of the blade with a variety of angles. Experimental testing requires expensive costs and a lot of time. The simulation carried out is a static simulation with the finite element method in the solidwork application with AISI 1045 material and 87.05 N force load. The blade with an angle of 310 is the best angle with the maximum value of stress at the connection of the shaft and knife with a value of 20.664 MPa and the displacement results are at a maximum value of 0.018 mm.